UNESCO'S MISSION IN THE DEVELOPMENT OF TRANSNATIONAL HIGHER EDUCATION - Наталія Авшенюк (Ivan Ziaziun Institute of Pedagogical Education and Adult Education of the NAES of Ukraine, 2020)
The article is devoted to the characterization of the constitutive influence of UNESCO on the transnational higher education formation at the end of the XX - the beginning of the XXI century, in particu-lar, to substantiate strategies for its development and quality assurance at the global and regional levels. Based on the study of a wide source base, UNESCO's role in the development of transnational higher educa-tion is uncovered though it has been firmly included in the structure of the international relations system in the field of internationalization of higher education as the institution of global educational policy of global scale. It is revealed that the main directions of the international organization's activity in the development of transnational higher education are: statistical data collection and classification; harmonization of the termi-nology apparatus; deepening knowledge of transnational higher education issues; development of recom-mendations for the transnational higher education management, ensuring its quality; creation of infor-mation exchange centers; forecasting and developing strategies for its development. It was established that on the international level, on the basis of the method of open coordination, the leading institutions of global regulation of education development have agreed and adopted normative documents on the quality assur-ance of transnational higher education, the unifying characteristics of which are: the basic principle of mu-tual trust between countries and respect for the diversity of higher education systems; quality management of transnational educational services; ensuring the detection of dishonest providers; recommendation focus on the activities of stakeholders: government, higher education institutions, educational services providers, student organizations, quality assurance and accreditation institutions, institutions for recognition of quali-fications and diplomas, professional associations of teachers, researchers, etc.